Mechanically prelithiated silicon nano alloy as highly engineered anode material. (20th December 2017) - Alaboina, Pankaj K.; Cho, Jong-Soo; Uddin, Md-Jamal; Cho, Sung-Jin
Abstract: Silicon (Si) anodes suffer from huge volume changes leading to cracking and pulverization impacting the battery life. To deliver high energy and long-term stability, we present a unique and facile prelithiated silicon nano alloy (SiNA) material with lithium stearate as reagent. Structurally controlled SiNA (in this work Si -iron (Fe)-manganese (Mn) combination) design with active Si surrounded by inactive buffer matrix to reduce mechanical deterioration during expansions was synthesized using a low-cost and low-temperature process relying on mechanical milling. Prelithiation was accomplished to compensate for the initial irreversible loss by pre-feeding with the lithium reagent to form a protective artificial solid electrolyte interphase (SEI) and prefill the mechanical crack voids of the SiNA to improve the mechanical properties necessary for long-term cyclability. The approach was to mechanically mix SiNA with lithium stearate followed by heat treatment above the melting point of lithium stearate to allow its easy diffusion with the surface and mechanical voids of the SiNA. Prelithiated SiNA exhibited enhanced physicochemical properties and featured boosted mechanical integrity characterized by nanoindentation. In overall, prelithiated SiNA revealed excellent electrochemical properties and long-term cycling stability addressed at significantly high loading (∼2 mg cm −2 ) and over 250 cycles, demonstrating its transformable potential to high energy applications.